Reye’s Syndrome: Issues, Clinical Manifestations, and Management - Pramudia, Prananda Rizki; Saraswati, Citra Ayu; Fildzani, Qashrina Vania; Srigede, Baiq Kayla; Lovely, Anjela Fatma; Zuhan, Arif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Reye's syndrome is a rare disease that has the potential to damage several organs, particularly the brain and liver. The exact cause remains unknown, but several cases suggest a link to viral and bacterial infections, especially Influenza and Varicella. The clinical symptoms of Reye's syndrome include altered consciousness, fever, seizures, lethargy, vomiting, tachycardia, respiratory rhythm disturbances, changes in muscle tone, altered reflexes, and reduced urine production. This study aims to understand the clinical characteristics and evaluate the effectiveness of management in patients with Reye's syndrome through a literature review. The findings indicate that Reye's syndrome frequently affects children following viral infections, with initial symptoms of vomiting and altered consciousness progressing to coma. Laboratory tests reveal elevated liver enzymes and hypoglycemia, while prompt management, such as stabilizing vital functions and managing intracranial pressure, can improve prognosis. In conclusion, Reye's syndrome requires rapid intervention to prevent further organ damage, and education on the risks of aspirin use in children with viral infections, along with early intervention, is crucial to reducing morbidity and mortality associated with this condition.